Illustrated flora of Tajikistan and adjacent areas - Nowak, Arkadiusz; Nobis, Marcin (Polish Botanical Society, 2020)
The Pamir-Alay Mountains are extremely diverse in terms of climate, landscape and habitat conditions. With one of the largest altitudinal amplitudes in the world, long gradients of precipitation and temperatures, different soil substrates and a diverse geology, the Pamir-Alai promotes a great number of plant species and diverse vegetation types. Currently almost 4,300 vascular plant species have been reported from the area. Almost 1,500 are endemics belonging to 60 families and 188 genera. The Pamir-Alai vegetation is fairly diverse and can be generally divided into 21 types: mesophilous deciduous forests, riverside forests, river-bed forests, xerothermophilous shrubs, subalpine coniferous forests, river-bed shrubs, meadows and pastures, segetal vegetation, alpine meadows and swards, steppes and so-called semi-savannas, xerothermophilous swards, xerothermophilous dwarf shrubs, desert and semi-desert vegetation, fen-spring vegetation, tallherbs, littoral vegetation, aquatic vegetation, scree and sliding rock vegetation, rock vegetation and salt-marsh vegetation. Our photographic guide includes vivid photograph of 1,864 species, as well as their distribution map, systematic position, biological and ecological features. The book is assigned for professional botanists and amateurs, students, plant lovers and tourists visiting Middle Asia or wanting to broaden their knowledge on the extraordinary flora of this region.